Clinicopathologic and proteomic characteristics of low-grade undifferentiated spindle cell sarcoma - Wei, Yani; Li, Hongjun; He, Shujin; Li, Min; Chen, Yongyu; Shi, Huijuan; Han, Anjia (Frontiers in Molecular Biosciences, 2025)
IntroductionUndifferentiated spindle cell sarcoma (USCS) is a rare and heterogeneous group without specific diagnostic, prognostic, or predictive markers. The clinicopathologic and proteomic characteristics of USCS remain largely unknown.MethodsBetween 2008 and 2024, we collected 14 low-grade USCSs and 104 undifferentiated pleomorphic sarcomas (UPSs). We conducted a comprehensive mass spectrometry (MS) proteomic analysis on USCSs and compared the clinicopathologic characteristics of low-grade USCSs and UPSs. More than 5600 proteins could be identified.ResultsLow-grade USCSs had 353 upregulated and 500 downregulated proteins compared to corresponding normal tissue. PHRF1, DIDO1, RAPH1, GGT7, and PHF14 exhibited overexpression in low-grade USCSs, whereas SERPINF2, TMEM40, FYCO1, COL2A1, and NPNT demonstrated low expression. The KEGG pathway enrichment analysis revealed that most of the enriched pathways in low-grade USCS were related to various amino acid and lipid metabolic. Correlating significantly changed proteins with their targeting medications revealed novel therapy options for low-grade USCSs. Furthermore, in comparison to UPSs, our findings indicate that low-grade USCSs may exhibit smaller sizes and a lower rate of distant metastasis. In summary, to the best of our knowledge, this is the first in-depth proteomic analysis to demonstrate a comprehensive investigation of the clinicopathological and proteomic characteristics of low-grade USCSs.ConclusionWe initially elucidated the characteristics of differential proteins, the pathways enriched, and their possible drug targets in low-grade USCSs. Data are available via ProteomeXchange with identifier PXD061644.